Impact of Bioconjugation on Structure and Function of Antibodies for Use in Immunoassay by Hydrogen-Deuterium Exchange Mass Spectrometry - Luckau, Luise; Groves, Kate; Blencowe, Chris; Scrimshaw, Sam; Dent, Alastair; Quaglia, Milena (Frontiers in Molecular Biosciences, 2022)
Monoclonal antibodies (mAbs) are widely used as analytical components in immunoassays to detect target molecules in applications such as clinical diagnostics, food analysis and drug discovery. Functional groups are often conjugated to lysine or cysteine residues to aid immobilization of mAbs or to enable their detection in an antibody antigen complex. Good assay performance depends on the affinity and specificity of the mAbs for the antigen. The conjugation reaction however can cause higher order structural (HOS) changes and ultimately affect the assay performance. In this study, four differently conjugated mAbs were selected as model systems and characterized by mass spectrometry. Particularly, intact protein analysis by liquid-chromatography mass-spectrometry (LC-MS) was performed to determine the amount and distribution of conjugation. Hydrogen deuterium exchange mass spectrometry (HDX-MS) experiments were carried out for the structural characterization of the conjugated mAbs. Immunoassay experiments were performed to monitor the effects of conjugation on the binding properties of the antibodies selected. Good agreement between the mass spectrometry and binding experiment results was found. Particularly, it was noted that the overall structural flexibility of the antibodies increases upon cysteine conjugation and decreases for lysine conjugation. The conjugation of mAbs with bulky functional groups tends to decrease the deuterium uptake kinetics due to induced steric effects. Overall, this study shows correlations between conjugation, structure and function of immunoassay antibodies and the benefits of mass spectrometry to improve understanding of the conjugation reaction and provide insights that can predict immunoassay performance.